Epidemiology and mapping of child road casualties. Issue 6 (16th February 2022) - Smith, Alexandra Celeste; Jones, Sarah J; Hanna, David
Abstract : Background: Paediatric trauma following road traffic collisions (RTCs) represents a significant public health burden. This study aims to influence road safety in Wales. Methods: Police (STATS19) and healthcare databases covering all or part of Wales were analysed, compared and mapped from 2017 to 2019 for RTCs involving children aged 0–16 years. Results: STATS19 under-reports RTCs, recording 1859 road traffic injuries (RTIs) for all Wales compared with 1170 RTIs at one tertiary hospital in South East Wales. Boys aged 11–16 years had the highest injury rates (92.2 per 100 000 population). Injuries peaked at school journey times. The rate ratio of injury was 2.0 (95% CI 1.7 to 2.4) for the most deprived compared with the least deprived areas. Conclusion: Improvements in data quality are essential to influence road policy. Improved road safety is needed in all communities but must be further enhanced in the most deprived areas, where the burden of injury is highest. Abstract : A short report presenting paediatric road traffic collision data from three sources in Wales. Compares reporting between datasets and discusses epidemiological factors associated with road traffic collisions.